2009
DOI: 10.1118/1.3075901
|View full text |Cite
|
Sign up to set email alerts
|

Application‐ and patient size‐dependent optimization of x‐ray spectra for CT

Abstract: Although x-ray computed tomography (CT) has been in clinical use for over 3 decades, spectral optimization has not been a topic of great concern; high voltages around 120 kV have been in use since the beginning of CT. It is the purpose of this study to analyze, in a rigorous manner, the energies at which the patient dose necessary to provide a given contrast-to-noise ratio (CNR) for various diagnostic tasks can be minimized. The authors used cylindrical water phantoms and quasianthropomorphic phantoms of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
152
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(159 citation statements)
references
References 46 publications
7
152
0
Order By: Relevance
“…The nested disk of the electron density phantom was made from plastic water (1.016 g/cc). The contrast‐to‐noise ratio (CNR) is an important index for the detection and diagnosis of structure and details of interest in CT,20 so CNR was used in this study to quantify the target detectability in both MDCT and CBCT. A circular region‐of‐interest (ROI) of 31 pixels was placed on the target and background regions in 11 slices (the central slice ±5 slices) to calculate the mean and standard deviation of HUs within ROI.…”
Section: Methodsmentioning
confidence: 99%
“…The nested disk of the electron density phantom was made from plastic water (1.016 g/cc). The contrast‐to‐noise ratio (CNR) is an important index for the detection and diagnosis of structure and details of interest in CT,20 so CNR was used in this study to quantify the target detectability in both MDCT and CBCT. A circular region‐of‐interest (ROI) of 31 pixels was placed on the target and background regions in 11 slices (the central slice ±5 slices) to calculate the mean and standard deviation of HUs within ROI.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Besides minimizing tube current, the reduction of the tube voltage is a potent option to reduce radiation dose. Such lowkilovolt protocols are used in cerebral perfusion CT in the evaluation of patients with stroke 16 and in pediatric CT. 17 In phantom 18 as well as in clinical studies, it has been demonstrated that this technique can also be used in chest and abdominal imaging in adults. [19][20][21][22][23][24] Lower tube voltage in CTA results in higher noise levels on one hand, but the attenuation of iodine is increased 25,26 on the other hand.…”
mentioning
confidence: 99%
“…The equal CNR requirement is not made when making a protocol change on a single scanner. To determine how the image contrast changes with beam energy, we have relied on the CT literature 11 , 16 , 17 . For example, if the CNR is desired to be kept constant but the kV is changed from 100 to 80, the contrast would increase by a factor of 1.32 (282 HU at 80 kV divided by 213 HU at 100 kV for iodine in a 25 cm phantom), according to Yu et al (11) For the example change of 100 to 80 kV, the noise needs to increase by a factor of 1.32 to keep the CNR constant (for iodine contrast imaging) and therefore the mA would need to change by (11.32)2=0.57.…”
Section: Methodsmentioning
confidence: 99%